2014
DOI: 10.1002/nau.22567
|View full text |Cite
|
Sign up to set email alerts
|

Association between self-reported urinary incontinence and musculoskeletal conditions in community-dwelling elderly women: A cross-sectional study

Abstract: This study showed that UI was significantly associated with musculoskeletal conditions, including LBP, and the combination of pain and OA. The risk of urge UI was greater with increasing severity of LBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 20 publications
(25 reference statements)
6
47
0
1
Order By: Relevance
“…In that study, an OR = 1.39 was found in women with comorbidities, confirming the increased risk of UI among women with other chronic diseases . An association between the prevalence of UI and the presence of multimorbidity indirectly reflects the progressive increase in life expectancy and its clinical/epidemiological implications, as confirmed by de Souza Santos Machado et al In our study, the presence of arterial hypertension also increased the risk of developing UI, as already demonstrated by Sensoy et al Similarly, other studies show that osteomuscular alterations common in elderly women, such as osteoarthritis, are among the factors associated with a higher prevalence of UI …”
Section: Discussionsupporting
confidence: 89%
“…In that study, an OR = 1.39 was found in women with comorbidities, confirming the increased risk of UI among women with other chronic diseases . An association between the prevalence of UI and the presence of multimorbidity indirectly reflects the progressive increase in life expectancy and its clinical/epidemiological implications, as confirmed by de Souza Santos Machado et al In our study, the presence of arterial hypertension also increased the risk of developing UI, as already demonstrated by Sensoy et al Similarly, other studies show that osteomuscular alterations common in elderly women, such as osteoarthritis, are among the factors associated with a higher prevalence of UI …”
Section: Discussionsupporting
confidence: 89%
“…Another important aspect is that UI not only impacts on the social life of older women [24] but also is related to lower handgrip strength and slower gait speed [25]. Taken together, the findings suggest that resistance exercise could be an accessible tool to improve the symptoms of urine loss, as well as other physical aspects relevant to the health of older women.…”
Section: Discussionmentioning
confidence: 85%
“…Most studies included only women; two included both men and women, and a further two were done with a male‐only population . One study considered storage and voiding symptoms, and four studies evaluated specific subtypes of incontinence . The studies all demonstrated that there was a statistically significant association between the diagnosis of urinary incontinence or urinary symptoms and low back pain, with adjusted odds ratios varying from 1.1 to 3.1.…”
Section: Resultsmentioning
confidence: 99%
“…Sometimes it is in the setting of an acute low back injury, and other times the urinary and back pain symptoms have a more gradual onset. Prior studies have suggested there is a link between low back pain and urinary incontinence, and this has been hypothesized to be mediated through pelvic floor dysfunction …”
Section: Introductionmentioning
confidence: 99%